2020
DOI: 10.1039/c9dt04619d
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory activity of superoxide dismutase mimics functionalized with cell-penetrating peptides

Abstract: A superoxide dismutase mimic was functionalized with three peptides: -R9, -RRWWRRWRR or -Fx-r-Fx-K (MPP). They were studied in intestinal epithelial cells in an inorganic cellular chemistry approach: quantification, distribution and bio-activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 61 publications
6
26
0
Order By: Relevance
“…Although it penetrates in this model, no activity was observed for this negatively charged porphyrin. Interestingly too, this study suggests that M40403 and EUK134 penetrate into cells and confirmed the previous results reported for Mn1 [9,103,107]. The different activities observed here may be related to different cellular localizations.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Although it penetrates in this model, no activity was observed for this negatively charged porphyrin. Interestingly too, this study suggests that M40403 and EUK134 penetrate into cells and confirmed the previous results reported for Mn1 [9,103,107]. The different activities observed here may be related to different cellular localizations.…”
Section: Resultssupporting
confidence: 91%
“…Because the ligand is toxic for the cells [9], the pro-inflammatory response observed may be due to the toxicity of the non-coordinated ligand. Note that in this model, MnCl 2 was previously assayed and found to be not active or proinflammatory [9,103,107]. After incubation at a higher concentration (100 µM), as expected, M40403 and MnTnBuOE-2-PyP 5+ were found more active than at 10 µM.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Manganese SOD mimics described in the literature include complexes with ligands such as porphyrins [14,[22][23][24][25][26][27][28], salens [29,30], cyclic polyamines [11,[31][32][33][34][35][36][37] phthalocyanines [38], or peptidyl ligands [39][40][41]. We have been developing a 1,2ethanediamine-centered ligand, called EnPI2 [42], inspired by the MnSOD-active site, with a coordination sphere consisting of three imidazoles and one phenolate, easily amenable to synthetic modulation [43][44][45][46]. Mn(II)-EnPI2, labeled Mn1, is a positively charged complex with a redox potential close to the optimal value for superoxide dismutation [42,44].…”
Section: Introductionmentioning
confidence: 99%
“…To date, the cellular accumulation of SOD mimics was usually examined by measuring the increase in the overall intracellular content in manganese using ICP-MS [46,[50][51][52], EPR [44][45][46], Raman [53], X-ray absorption spectroscopy [36], and X-ray fluorescence imaging [13,36,[44][45][46] or by detecting the cellular uptake using UV quantification of Mn porphyrin via the Soret band area [16,54] or of fluorescently labeled SOD mimics using laser confocal microscopy [36,40,46,55]. At best, these techniques enable determining the intracellular distribution of the ligand, complexes, and/or Mn.…”
Section: Introductionmentioning
confidence: 99%